Opportunities within the Agri-food System to Encourage a Nutritionally Balanced Diet– Part II. Issue 6 (18th August 2021) - Van Pamel, Els; Cnops, Gerda; Van Droogenbroeck, Bart; Delezie, Evelyne C; Van Royen, Geert; Vlaemynck, Geertrui Mml; Bekaert, Karen Mm; Roldan-Ruiz, Isabel; Crivits, Maarten; Bernaert, Nathalie; De Block, Jan; Duquenne, Barbara; et al.
ABSTRACT: The field-to-fork concept comprises opportunities for providing consumers with nutritious and health-beneficial food in order to meet the growing interest in health-beneficial foods and to counteract the increase of diet-related diseases worldwide. While raw plant-/animal-based starting material is considered as the primary source of such compounds (see Part I), waste fractions from this primary biomass are additional sources. Opportunities hidden in such fractions are described in the first part of this review Part II. Additionally, specific opportunities further down the field-to-fork system are explored, namely those from processing technologies for plant- and animal-derived foods (e.g. application of heat, pressure, fermentation, etc.). Potential health benefits of raw materials can indeed be positively or negatively influenced by processing whether mild or intense. Processing may affect matrix-associated parameters like density, nutrient interactions, etc. and as such, play an important role for nutrient stability and bioavailability. In addition to attempts to maintain/augment the amounts of health-beneficial compounds within food commodities/products along the primary production and processing chain, opportunities such as concerted actions of the food industry aiming at reducing the levels of certain nutrients (e.g. sugar/salt/fat) can also be explored or applied within the framework of encouraging a balanced dietary pattern.